2020
DOI: 10.33963/kp.15070
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and prevalence of risk factors for coronary artery disease in patients after the first and repeated percutaneous coronary intervention

Abstract: BACKGROUND Percutaneous coronary intervention (PCI) is an effective method for the treatment of coronary artery disease (CAD) that allows for a short hospital stay and fast recovery. It has been shown that PCI is a predictor of nonattendance at cardiac rehabilitation and correlates with poor adherence to lifestyle changes. AIMS The study was conducted to evaluate the influence of education offered during PCI -related hospitalization on knowledge, awareness, and prevalence of self -reported risk factors for CAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Our results are in agreement with and greatly extend results from previous studies (e.g., Crowley et al 2015;Kotseva et al 2019;Molloy et al 2014;Peersen et al 2017;Urbinati et al 2014;Wójcicki et al 2020). For example, recent reports suggest that 40-50% of patients with established cardiovascular diseases do not consistently take their recommended medications, suggesting that non-adherence is a common occurrence among these individuals (Crowley et al 2015;Molloy et al 2014).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in agreement with and greatly extend results from previous studies (e.g., Crowley et al 2015;Kotseva et al 2019;Molloy et al 2014;Peersen et al 2017;Urbinati et al 2014;Wójcicki et al 2020). For example, recent reports suggest that 40-50% of patients with established cardiovascular diseases do not consistently take their recommended medications, suggesting that non-adherence is a common occurrence among these individuals (Crowley et al 2015;Molloy et al 2014).…”
Section: Discussionsupporting
confidence: 93%
“…For example, recent reports suggest that 40-50% of patients with established cardiovascular diseases do not consistently take their recommended medications, suggesting that non-adherence is a common occurrence among these individuals (Crowley et al 2015;Molloy et al 2014). Wójcicki et al (2020) recently showed that patients with a cardiovascular disease experience insufficient changes in individual lifestyle after a percutaneous coronary intervention, and report an overall poor awareness of the cardiovascular risk factors. Moreover, a large European cross-sectional study on 8261 patients interviewed approximately 1 year after their first cardiac event showed that most of them failed to achieve the healthy lifestyle targets set by the Joint European Societies of Cardiology (Kotseva et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional cardiac rehabilitation programs are less effective for patients with a lower level of education and tend to be less efficient in patients after non-emergency myocardial revascularization compared to subjects with acute coronary syndromes [24,25]. Indeed, several recent initiatives have aimed at improving cardiovascular risk through education-based secondary prevention programs [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…According to World Health Organization data, up to 80% of premature CVD-related deaths could be avoided with proper prevention introduced in time [ 2 ]. Previously reported studies have indicated no differences in the level of knowledge about CVD and risk factor control between patients with a history of one or several percutaneous coronary interventions (PCI) [ 3 , 4 ]. A short hospitalization period or low awareness about the severity of the disease among patients undergoing fast and convenient procedures might explain this finding.…”
Section: Introductionmentioning
confidence: 99%